Mitochondrial dysfunction and metabolic reprogramming induce macrophage pro-inflammatory phenotype switch and atherosclerosis progression in aging - Vendrov, Aleksandr E.; Lozhkin, Andrey; Hayami, Takayuki; Levin, Julia; Silveira Fernandes Chamon, Jamille; Abdel-Latif, Ahmed; Runge, Marschall S.; Madamanchi, Nageswara R. (Frontiers in Immunology, 2024)
Aging increases the risk of atherosclerotic vascular disease and its complications. Macrophages are pivotal in the pathogenesis of vascular aging, driving inflammation and atherosclerosis progression. NOX4 (NADPH oxidase 4) expression increases with age, correlating with mitochondrial dysfunction, inflammation, and atherosclerosis. We hypothesized that the NOX4-dependent mitochondrial oxidative stress promotes aging-associated atherosclerosis progression by causing metabolic dysfunction and inflammatory phenotype switch in macrophages. Young (5 months) Nox4-/-/Apoe-/- and Apoe-/- mice had comparable aortic atherosclerotic and brachiocephalic artery lesion cross-sectional areas. Aged mice (16 months) showed significantly increased lesion area compared with young mice. However, aged Nox4-/-/Apoe-/- showed notably lower lesion areas than Apoe-/- mice. Compared with Apoe-/- mice, atherosclerotic lesions in aged Nox4-/-/Apoe-/- showed reduced cellular and mitochondrial ROS and oxidative DNA damage, lower necrotic core area, higher collagen content, and decreased inflammatory cytokine expression. Immunofluorescence and flow cytometry analysis revealed that aged Apoe-/- mice had a higher percentage of classically activated pro-inflammatory macrophages (CD38+CD80+) in the lesions. On the other hand, Nox4-/-/Apoe-/- mice had a significantly higher proportion of alternatively activated pro-resolving macrophages (EGR2+/CD163+CD206+) in the lesions, with an increased CD38+/EGR2+ cell ratio compared with Apoe-/- mice. Mitochondrial respiration assessment revealed impaired oxidative phosphorylation and increased glycolytic ATP production in macrophages from aged Apoe-/- mice. In contrast, macrophages from Nox4-/-/Apoe-/- mice were less glycolytic and more aerobic, with preserved basal and maximal respiration and mitochondrial ATP production. Macrophages from Nox4-/-/Apoe-/- mice also had lower mitochondrial ROS levels and reduced IL1β secretion; flow cytometry analysis showed fewer CD38+ cells after IFNγ+LPS treatment and more EGR2+ cells after IL4 treatment than in Apoe-/- macrophages. In aged Apoe-/- mice inhibition of NOX4 using GKT137831 significantly reduced macrophage mitochondrial ROS and improved mitochondrial function resulting in decreased CD68+CD80+ and increased CD163+CD206+ lesion macrophage proportion and attenuated atherosclerosis. Our findings suggest that increased NOX4 in aging drives macrophage mitochondrial dysfunction, glycolytic metabolic switch, and pro-inflammatory phenotype, advancing atherosclerosis. Inhibiting NOX4 or mitochondrial dysfunction could alleviate vascular inflammation and atherosclerosis, preserving plaque integrity.